Cardiogenic shock after use of fluoroamphetamine confirmed with serum and urine levels. (December 2014) - Al-Abri, Suad; Meier, Kathryn H.; Colby, Jennifer M.; Smollin, Craig G.; Benowitz, Neal L.
Abstract Context. 4-Fluoroamphetamine (4-FA) is a para-substituted phenethylamine-type synthetic stimulant that has in recent years gained popularity through internet blogs and market share according to confiscated drug data. No serious toxicity has previously been reported. We report a case of a young man who developed severe toxicity and cardiogenic shock after using 4-FA, with laboratory confirmation. Case details. An 18-year-old man presented to the emergency department with vomiting, shortness of breath, chest tightness, and altered mental status about 5 h after using a new and unfamiliar street drug. Two days prior, he had received naltrexone intramuscular injection as part of an opioid addiction treatment program and was taking fluoxetine and trazodone. Five hours after presentation, he developed cardiogenic shock requiring intraaortic balloon pump, inotropic and ventilatory support. An echocardiogram showed left ventricular (LV) hypokinesia, sparing the apex and ejection fraction (EF) = 10%. Comprehensive toxicology serum testing revealed FA, naproxen, trazodone, and cotinine. The 4-FA urine level was 64, 000 ng/ml and serum level was 118 ng/ml. With slow recovery, the patient was discharged after 2 weeks of hospitalization. Discussion. Although no previously reported 4-FA clinical poisoning cases have been published for comparison, by examining 4-FA pharmacology compared with other stimulant drugs, and given this patient's presentation and echocardiogram suggestive of reverse takotsubo cardiomyopathy we suspect the toxic mechanism was an acute cardiomyopathy caused by 4-FA catecholamine-induced myocarditis and/or small vessel myocardial ischemia. Conclusion. Recreational use of 4-FA may present with life threatening toxicity including cardiomyopathy, cardiogenic shock, and pulmonary edema.